Use of Nanoparticles as Materials to Prevent Dental and Oral Diseases - Pindobilowo; Dwi Ariani; Dewi Puspitasari (PT FORMOSA CENDEKIA GLOBAL, 2024)
Introduction: Nanoparticles can be applied in various fields of dentistry such as preventive dentistry, dental caries, periodontal disease, restorations, pulp and periapical lesions, oral candidiasis, denture stomatitis, hyposalivation, and head, neck and oral cancer. The purpose of this paper is to determine the uses and benefits of nanoparticles in the field of dentistry. Methodology: using the Narrative Review method based on journal databases including: PubMed, EBSCO, ResearchGate, and ProQuest from 2016 to 2022. Conclusion: Beneficial nanoparticles can improve the diagnosis, prevention, and treatment of various oral diseases, including dental caries, periodontal disease, lesions pulpal and periapical, oral candidiasis, denture stomatitis, hyposalivation, and head, neck, and oral cancer.